Pretreatment strategies to improve crude glycerol utilisation and metabolite production by Aspergillus terreus - Abd Rahim, Muhamad Hafiz; Hasan, Hanan; Jitming, Elicia Lim; Samrani, Phebe K. (Hindawi, 2019)
Crude glycerol (CG) can be used as a substrate for microbial bioconversion. However, due to presence of many impurities, manymicroorganisms are unable to utilise this substrate efficiently. +e present study is trying to improve CG using as the feedstock ofAspergillusterreusfor the production of lovastatin, (+)-geodin, and sulochrin. +e CG was pretreated chemically (solvents) andphysically (activated carbon (AC) and water softener (WS)) to separate most of the impurities from the CG. For solventpretreatments, petroleum ether (PE) produced the largest increase of lovastatin (92.8%) when compared to positive control andpure glycerol (PG) and up to 820% when compared to negative control (CG). In contrast, diethyl ether (DE) produced the largestincrease in (+)-geodin at 80.81% (versus CG) and 176.23% (versus PG). +e largest increase in toluene (Tol) was observed insulochrin production, at 67.22% (versus CG) and 183.85% (versus PG). For physical pretreatments, the pattern of metaboliteproduction in AC (lovastatin: 20.65 mg/L, (+)-geodin: 7.42 mg/L, sulochrin: 11.74 mg/L) resembled PG (lovastatin: 21.8 mg/L,(+)-geodin: 8.60 mg/L, sulochrin: 8.18 mg/L), while WS (lovastatin: 11.25 mg/L, (+)-geodin: 15.38 mg/L, sulochrin: 16.85 mg/L)resembled CG (lovastatin: 7.1 mg/L, (+)-geodin:17.10 mg/L, sulochrin:14.78 mg/L) at day 6 of fermentation. +ese results indicatethat solvent pretreatments on CG are excellent for metabolites production inA. terreus, depending on the solvents used. Incontrast, physical pretreatments are only feasible for (+)-geodin and sulochrin production. +erefore, different strategies can beemployed to manipulate theA. terreusbioconversion using improved CG by using a few simple pretreatment strategies.